Adverse events in children and adolescents undergoing allergen immunotherapy for respiratory allergies—Report from the Allergen Immunotherapy Adverse Events Registry (ADER), a European Academy of Allergy and Clinical Immunology taskforce - Julijana Asllani; Dimitrios Mitsias; George Konstantinou; Eris Mesonjesi; Fatmira Xhixha; Esmeralda Shehu; George Christoff; Katia Noleva; Michael Makris; Xenofon Aggelidis; Mirjana Turkalj; Erceg Damir; et al. (Clinical and Translational Allergy, 2023)
Abstract Background Although it has been shown that allergen immunotherapy (AIT) is well‐tolerated in children, systematic and prospective surveillance of AIT safety in real life settings is needed. Methods The multinational Allergen Immunotherapy Adverse Events Registry (ADER) was designed to address AIT safety in real life clinical practice. Data on children ≤18 years old with respiratory allergies undergoing AIT were retrieved. Patient‐ and AIT‐related features were collected and analyzed. The characteristics of adverse events (AE) and risk factors were evaluated. Results A total of 851 patients, 11.3 ± 3.4 years old, with rhinitis only (47.6%); asthma and rhinitis (44.5%); asthma (7.9%), receiving 998 AIT courses were analyzed. Sublingual immunotherapy (SLIT) accounted for 51% of the courses. In 84.5% of patients only one AIT treatment was prescribed. Pollen was the most frequent sensitizer (57.1%), followed by mites (53.4%), molds (18.2%) and epithelia (16.7%). Local and systemic AEs were reported in 85 patients (9.9%). Most AEs (83.1%) were mild and occurred in <30 min (87%). Respiratory and cutaneous symptoms were more frequent. Only 4 patients (0.47%) had severe AE (none after 6 weeks of maintenance). The risk of AE was higher in patients undergoing SCIT. Conclusions AIT is safe and well tolerated in children and adolescents with respiratory allergies in real‐life clinical practice. Though SCIT is more prone to AE compared to SLIT, overall severe reactions are rare and occur during build‐up and early maintenance.